The trajectory of development in Latin America : A critical perspective from its cultural matrix - Estenós Loayza, Alejandro (2007)
Since the beginning of its republican life, the Latin American peoples have made strenuous efforts to position themselves among those who bear the label of modern and developed. The repeated failures of these attempts were associated with deep questioning about the possibility and convenience of assuming progress and development projects, since the cultural characteristics of this part of the continent were very different from the original cultural contexts of said projects. Since then, at different times of acute social crisis in the region, heated debates have arisen around the cultural difficulties of local peoples in assuming as their own the processes of progress and development that Western modernization brought with it. In the midst of these controversies, polarized theoretical and pragmatic positions have emerged that decoded the relationship between modernization, development and culture either in terms of excessive a-historical and a-cultural simplism or else in antithetical and irreconcilable terms. For almost two centuries, these positions have allowed a vision of one's own identity in terms of inferiority that needs —at all costs— the modernizing project or, on the contrary, an essentially different vision of identity, and therefore , incapable of effectively assuming any modernizing process.